2022
DOI: 10.3390/rel13050465
|View full text |Cite
|
Sign up to set email alerts
|

Faithful Stewards of God’s Creation? Swedish Evangelical Denominations and Climate Change

Abstract: Studies from the United States (U.S.) show that opposition to climate policy is strong among some Christian groups, especially White evangelical Protestants. Much of this opposition is channelled through organisations such as the Cornwall Alliance, which argue against climate measures on religious, economic and what they claim to be science-based grounds. In the present study, we investigated to what extent these convictions were present among Swedish evangelical denominations. Representatives from the Evangel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
(55 reference statements)
0
2
0
1
Order By: Relevance
“…The susceptibility to believe misrepresentations is also explored. Multiple studies focus on worldviews of climate science denying actors and find multiple motivations and predictors such as libertarian ideologies ( Lewandowsky, 2021a ), political identities ( Feygina et al, 2010 ; Whitmarsh and Corner, 2017 ), religious evangelism ( Edvardsson Björnberg and Karlsson, 2022 ), anti-feminist and anti-immigrant values ( Jylhä et al, 2020 ) and social construction and emotional protections ( Norgaard, 2006a ). Much of this literature addresses the political implications, particularly in terms of rejection of climate policy.…”
Section: Climate Denialmentioning
confidence: 99%
“…The susceptibility to believe misrepresentations is also explored. Multiple studies focus on worldviews of climate science denying actors and find multiple motivations and predictors such as libertarian ideologies ( Lewandowsky, 2021a ), political identities ( Feygina et al, 2010 ; Whitmarsh and Corner, 2017 ), religious evangelism ( Edvardsson Björnberg and Karlsson, 2022 ), anti-feminist and anti-immigrant values ( Jylhä et al, 2020 ) and social construction and emotional protections ( Norgaard, 2006a ). Much of this literature addresses the political implications, particularly in terms of rejection of climate policy.…”
Section: Climate Denialmentioning
confidence: 99%
“…However, it is difficult to determine whether these views are shared among different religious groups and in different regions. For example, most representatives from Evangelical Christian Denominations in Sweden felt that addressing climate change was important and identified themselves as being responsible to take action (33). Additionally, non-Judeo-Christian religions may have stronger pro-environmental commitments (15), as suggested by an Australian study which found that Buddhists were more likely, and Christians less likely, to endorse climate change beliefs compared to non-religious individuals (34).…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de no poder concretar una entrevista con representantes de iglesias evangélicas, los entrevistados reconocieron que pueden trabajar en 140 conjunto con sus líderes en causas ecológicas. Esto está en sintonía con estudios globales que indican que el negacionismo climático asociado a estas agrupaciones se debe a fenómenos políticos locales, como en EEUU y Brasil, y no representa una cualidad intrínseca del evangelismo (Edvardsson Björnberg & Karlsson, 2022). Sin embargo, la realidad en el campo es que la religión cuenta con gran influencia a la vez que es el mayor factor de tensiones y conflictos internos.…”
Section: Discusión Y Conclusionesunclassified